Preparation of Magnesium Oxide Nanoparticles from a Sea Water Bittern as an Antibacterial Agent Against Escherichia coli - Ningrum, Ananda Nurmalia Kusuma; Jumaeri, Jumaeri (Universitas Negeri Semarang, 2022)
Bittern is a by-product of the manufacture of salt which has a high MgCl2 content. Bittern can produce Mg(OH)2 which is one of the important precursors of MgO. MgO compounds can be used as an antibacterial against E. coli that contaminates food. This research aims to synthesize MgO nanoparticles as well as antibacterial testing against E.coli. Synthesis was performed using the wet precipitation method with bittern reaction and technical NaOH with volume ratio 1: 1 which was then calcined at 5000C, 6000C, and 7000C. Characteristic tests using XRD, FT-IR, and SEM and antibacterial activity testing using disc diffusion method with concentrations of 10 mg/mL, 20 mg/mL, and 30 mg/mL. Inhibition is measured based on the size of the diameter of the bacterial growth inhibition area. Based on the results of the XRD test showed the result of pure MgO with a crystalline size of 6.3 nm; 7.2 nm; and 15.8 nm at each calcination temperature, the FT-IR test produced an absorption at a wave <450 cm-1 indicating the presence of MgO clusters and the SEM test produced a nano-structure that was almost round, dense as a cavity in the grains. The results of testing the antibacterial activity of MgO nanoparticles showed inhibitory activity with a diameter range between 5 mm - 8 mm which was interpreted in the medium category. The best inhibition value is 5000C calcination at a concentration of 30 mg/ml of 7.87 mm.